Optical Supercomputing 4th International Workshop, OSC 2012, in Memory of H. John Caulfield, Bertinoro, Italy, July 19-21, 2012. Revised Selected Papers - Dolev, Shlomi; Oltean, Mihai; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Workshop on Optical SuperComputing, OSC 2012, held in Bertinoro, Italy, in July 2012. The 11 papers presented together with 11 invited papers were carefully reviewed and selected for inclusion in this book. Being an annual forum for research presentations on all facets of optical computing for solving hard computation tasks, OCS addresses the following topics of interest: design of optical computing devices, electro-optic devices for interacting with optical computing devices, practical implementations, analysis of existing devices and case studies, optical and laser switching technologies, applications and algorithms for optical devices, alpha particles, X-rays and nano-technologies for optical computing.
Design of optical computing devices -- Electro-optic devices for interacting with optical computing devices -- Practical implementations -- Analysis of existing devices and case studies -- Optical and laser switching technologies -- Applications and algorithms for optical devices -- Alpha particles, X-rays and nano-technologies for optical computing.
Keywords: Computer science; Information theory; Electronic data processing; Quantum theory; Computer Science; Computing Methodologies; Quantum Information Technology, Spintronics; Quantum Physics; Quantum Optics; Laser Technology, Photonics; Theory of Computation